ANALISIS NILAI EDUKATIF TRADISI ROKAT TASE’ MASYARAKAT PESISIR DESA KALIBUNTU KABUPATEN PROBOLINGGO DALAM PERSPEKTIF ILMU PENGETAHUAN SOSIAL - Udkhuli Jannati; Abu Yazid Adnan Quthny; Mahfudz Sulaiman (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Rokat Tase’ tradition is a cultural heritage of coastal communities that not only contains traditional and spiritual values, but also various educational values in social life. This tradition, which is still preserved by the people of Kalibuntu Village, Probolinggo Regency, symbolizes gratitude, togetherness, and the concern of coastal communities for their culture and surrounding environment. This study aims to analyze the educational values contained in the Rokat Tase’ tradition, the forms of implementation of educational values in the social life of coastal communities, and their relevance to Social Studies (IPS) learning. This research used a qualitative method with a case study approach. Data collection techniques were carried out through observation, interviews, and documentation involving informants consisting of the village head, community leaders, religious leaders, fishermen, Social Studies teachers, and the younger generation. The results showed that the Rokat Tase’ tradition contains religious values, mutual cooperation, togetherness, preservation of local culture, and environmental awareness. These values are implemented in the social life of the community through mutual assistance, deliberation, social solidarity, and the preservation of coastal cultural traditions. In addition, the Rokat Tase’ tradition is relevant to Social Studies learning because it can be used as a contextual learning resource related to the social, cultural, and environmental life of the community.